EFFECT OF WORKLOAD ON NURSES’ PERFORMANCE IN DELIVERING NURSING CARE IN LOW CARE INPATIENT UNITS OF DR. SAIFUL ANWAR HOSPITAL EAST JAVA PROVINCE: THE MODERATING ROLE OF WORK VALUES - Hidayati, Khusnul; Wardhani, Viera; Ratri, Devita Rahmani (Universitas Brawijaya, 2025)
High workloads, the complexity of nursing tasks, declining care quality, increased risk of medical errors, and reduced patient satisfaction are persistent challenges in hospitals that require strategic solutions. Work values may serve as motivational factors that encourage nurses to perform optimally, particularly under stressful conditions. This study aimed to analyze the effect of workload on nurse performance in delivering nursing care in low-care inpatient units, by considering work value as a potential moderating variable. This observational analytical study used a cross-sectional design. Data were collected from 195 nurses using proportional cluster random sampling based on unit assignment. Instruments included a demographic questionnaire, NASA-TLX to assess workload, an adapted career value scale to evaluate work values, and a nurse performance questionnaire developed from nursing practice standards. Data collection was conducted via Google Forms, and Partial Least Squares (PLS) moderation analysis was used to examine the relationships between variables. The results showed that most nurses experienced a moderate workload (49.7%) and demonstrated sufficient performance (78.5%). The highest contributing work value dimensions were intrinsic value and the competence sub-dimension. Workload and work value had a significant direct effect on nurse performance, but work value did not moderate the relationship between workload and performance. In conclusion, increased workload and stronger work values are associated with improved nurse performance.